Immunosuppressive effect of PLGA-FK506-NPs in treatment of acute cardiac rejection via topical subcutaneous injection - Cheng Deng; Qiaofeng Jin; Ya Wu; Huiling Li; Luyang Yi; Yihan Chen; Tang Gao; Wenyuan Wang; Jing Wang; Qing Lv; Yali Yang; Jia Xu; et al. (Taylor & Francis Group, 2021)
FK506, a first-line immunosuppressant, is routinely administered orally and intravenously to inhibit activation and proliferation of T cells after heart transplantation (HT). Current administration route is not conducive enough to exert its efficacy in lymphatic system. Herein, we proposed that subcutaneous (SC) administration of FK506-loaded nanoparticles (PLGA-FK506-NPs) would be valuable for treating acute rejection after HT. The biodistribution and pharmacokinetic study revealed that it could effectively deliver FK506 to the lymph nodes (LNs) due to their suitable particle size, especially in inguinal LNs. Subsequently, the therapeutic efficacy of PLGA-FK506-NPs on the HT model was evaluated using intravenous (IV), intragastric (IG), or SC injection. Histopathological analysis revealed that 80% of allografts exhibited only grade 1R rejection with negligible lymphocyte infiltration in the SC group. The IV group exhibited 40% 1R rejection with mild lymphocyte infiltration and 20% grade 3R that require further intervention, and the IG group exhibited grades 40% 3R rejection with more lymphocyte infiltration. Moreover, the infiltration of T cells and the secretion of IL-2 and IFN-γ were significantly reduced in the SC group compared with the IG or IV group. The mean survival time (MST) further revealed that 50% of grafts treated with PLGA-FK506-NPs via SC injection survived longer than IG and IV groups. Moreover, the MST of single-dose SC injection of PLGA-FK506-NPs demonstrated that it would effectively reduce the required dose for a similar therapeutic effect. Overall, these results indicate that SC administration of PLGA-FK506-NPs is a more effective route for chronic FK506 treatment.